Improving Employee Engagement and Team Development through the Implementation of Flexible and Adaptive Situational Leadership - Rojak, Jeje Abdul; Darmawan, Didit (Journal of Social Science Studies, 2023)
Situational leadership has a significant impact on employee engagement and team development in organizations. This leadership theory emphasizes the importance of leaders to adapt their style according to the conditions, abilities, and needs of employees. Leaders who are flexible in choosing the right approach for a given situation can create a more productive and collaborative work environment. By approaching employees individually and adapting their leadership style to the circumstances at hand, employee engagement can be improved, and team development can run smoothly. High engagement improves motivation, work quality, and builds a more solid team. Meanwhile, good team development can contribute to achieving organizational aims more efficiently. It is important for leaders to have emotional intelligence and the ability to assess situations well in order to manage teams effectively. Sustainable training and organizational support to strengthen these skills are needed for optimal implementation of situational leadership. This will bring long-term benefits to both individual development and overall organizational success.